(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This paper explores the concept of ethical branding and its link to corporate goodwill. Brands have traditionally been studied only as an economic construct. Brands, as a social construct have not yet been fully understood due to the lackof research. A corporate brand is a vital part of the corporate goodwill management. An ethical brand enhances the firms goodwill; such goodwill reinforces the brand in turn. On the other hand, any unethical behaviour will severely damage or even destroy the total intangible asset as evidenced by the recent high profile corporate scandals. Ethical branding could provide thecompany with a differential advantage as agrowing number of consumers become more ethically conscious.